La falta de fortaleza y los síntomas neuróticos - Seligmann, Zelmira (Sapientia, 2014)
The virtue of fortitude is primarily concerned with the fear of the difficult, things that can prevent the will to obey reason. But not only containing fear but also attacking with moderation. Studying the vices opposed to the virtue of fortitude we can see the similarity with neurotic symptoms. Fear is very important to them, as an escape from reality, which is feared by failing to impose his will to power, and the fear of failure. The pride is in neurosis that manifestation of superiority that A. Adler called desire of feeling personality, and indicates the compensation is done with a sense of inferiority. Ambition is the main feature of neurosis for A. Adler psychiatrists and other studious. Also appear frequently in the structure of pathological personality opposites magnanimity vices, conceit, cowardice, lack of patience and perseverance in good, etc. The virtuous life, and especially the virtue of fortitude, is the foundation of mental health.